Innovation ecosystems in health and care: the Andalusian Reference Site as an example - Carriazo, A. M.; Alonso-Trujillo, F.; Vázquez-Granado, F. J.; Túnez, I.; Del Moral-Leal, M. L. (Frontiers in Medicine, 2024)
Innovation ecosystems foster collaboration between academia, industry, public bodies, and civil society to drive technological and social advancements.• The European Innovation Partnership on Active and Healthy Ageing (EIP on AHA), launched in 2012, aimed to extend healthy life years, improve healthcare efficiency, and stimulate economic growth. • Reference Sites (RSs) and Action Groups (AGs) were key components, with RSs adopting collaborative approaches to improve health outcomes. • Andalusia, Spain, achieved top recognition across multiple EIP on AHA calls for its digital health strategies and strong Quadruple Helix collaboration. • In 2022, Andalusia's self-assessment using the SCIROCCO tool highlighted strengths in digital transformation and citizen empowerment. • Andalusia's innovative practices in health have contributed to regional improvements in healthcare efficiency, life expectancy, and research initiatives.